Exploring the Factors Perceived to be Inhibiting the Realisation of the Objectives of the Ghana Alternative Market (GAX) - Acquah-Sam, Emmanuel (European Scientific Journal, ESJ, 2019)
The Ghana Alternative Market (GAX) was established in 2013 to provide equity financing avenue for the development of SMEs and startups in Ghana. However, after six years of its establishment, the market is still unable to attract adequate listing of SMEs and startups. This study explored the factors perceived to be inhibiting the realisation of the objectives of the GAX, and its target of listing fifty firms by the end of 2020. Frequency distribution, bivariate correlations and multiple regression techniques were explored in this study. The correlation analysis shows that “extent of objective realisation” is significantly associated with “achievement of target by the end of 2020”, “perceived importance” of GAX, and “inadequate information” on GAX, but is not correlated significantly with the other variables at 5% level of significance. The regression analysis revealed that fear of failure of small and medium businesses and startups and the low-income situation of prospective investors make negative influences on the degree to which the objective of GAX could be met. Thus, the degree to which the objective of GAX is met decreases as investors’ fear of failure and low-income situations increase. Taken into consideration the fact that only five (5) companies have been listed on the GAX since its inception, and the fact that only a few months remain till the end of 2020, it seems very difficult for the authorities of GAX to attain its target of listing 50 firms by the end of 2020. It is recommended that more time and efforts are needed for the realisation of its objectives. The officials of Ghana Stock Exchange (GSE) and GAX must intensify education on the sector to boost the confidence of owners of SMEs and startups in the operations of the sector. Again, the government of Ghana must improve economic conditions in Ghana to increase the real incomes of workers in Ghana so as to help more people buy securities of listed SMEs and startups. The costs and requirements for listing on the GAX must be scaled down further. The government of Ghana must find the possibility of synchronising the activities of National Entrepreneurship and Innovation Plan (NEIP), Microfinance and Small Loans Centre (MASLOC) and GAX to reduce duplication of efforts and to ensure efficient allocation of financial resources to SMEs and startups in Ghana.